Effectiveness of a participatory action oriented training intervention approach among harvesters in oil palm plantation - Ng, Yee Guan; Mohd Tamrin, Shamsul Bahri; Ismail, Ismi Arif; Ananta, Gede Pramudya; Hashim, Zailina; Mohd Yusoff, Irwan Syah; Md Deros, Baba; Abu Bakar, Shahriman; Rambely, Azmin Sham (Science Publications, 2014)
Consistent with the global demand for palm oil, the intensified upstream harvesting activities of oil palms fresh fruit bunches, despite the harvesters evidences of various ergonomics risk factors leading to musculoskeletal disorders should be a cause for concern. Thus, this study describes the effectiveness of a modified and locally adapted Participatory Action-Oriented Training intervention program in improving the working environment of the harvesters. A training program modified and customized to the harvesters working in oil palm plantation consist of 3 primary instrument (awareness video, interactive lecture and action checklist) with 3 reinforcing activities (to increase knowledge, enhance understanding and practical application). Based on the result of post-intervention assessment, the self-reported prevalence of MSD and KAP score among Intervention Group (IG) did not significantly differ from Control Group (CG). Instead of decreasing, the prevalence of MSD in the past 12 months and 7 days increased within IG. Qualitative findings in this research show that the negative psychosocial and organizational climate has severely affected the implementation of PAOT rendering the effect of the intervention approach. The interventions were ineffective on the IG as this study suffers from various situational barriers as obstacles to benefit the full extent of PAOT advantages.